TECHNICAL PROBLEMS IN THE REVIEWING OF GOVERNMENT REGULATION IN LIEU OF LAW (PERPPU) AT THE CONSTITUTIONAL COURT FROM THE PERSPECTIVE OF LEGAL CERTAINTY - Taufikkurrahman Upik; Slamet Suhartono; Syofyan Hadi (IBLAM LAW REVIEW, 2024)
The need for formal legal sources in constitutional activities in public life cannot be ascertained due to a country's dynamics and political conditions. It is still also related to the need for regulatory provisions that align with current conditions. Government Regulations in Lieu of Law (PERPPU) are issued by the President in response to compelling urgencies, leveraging his constitutional authority to enact such regulations. Since PERPPU is a subjective product of the President, as mandated by the 1945 Constitution, it must be immediately reviewed by The House of Representatives (DPR) for approval or revoked if rejected. With the issuance of the PERPPU, certain parties may undoubtedly feel constitutionally disadvantaged. In such cases, the way that can be taken is to conduct a judicial review of the Constitutional Court as has been established in legal precedent. This research includes legal research. It is called legal research because the object of research is related to law. The type of research used is normative juridical. The approaches used in this research are the statute, conceptual, and case approaches. The results showed that many cases of PERPPU reviewing at the Constitutional Court lost the object of reviewing because it was enacted into law by the DPR. The loss of reviewing object PERPPU reviewing at the Constitutional Court becomes a technical problem in PERPPU reviewing that must be anticipated in the procedure for reviewing at the Constitutional Court.